Investigación e implementación del protocolo IPv6 en la infraestructura de la red existente del Área de la Energías, las Industrias y los Recursos Naturales no Renovables como propuesta hacia la migración a Internet 2. - Burneo Nieto, Gabriela judith (2008)
This work presents an investigation of the new Internet protocol, known as IPv6 (Internet Protocol Version 6). This protocol assumes better quality, security and manageability as added to the larger address space, which is listed as the basic idea of ​​the creation of this new technology features. The objective pursued advanced networks is another point that supports the implementation of this new technology, the idea is to facilitate the advancement of technologies and new Internet applications. This project has started in the US as Internet2, and continued in other countries with other names, but the essence is the same, providing national, regional and international academic institutions of the resources needed to develop new learning tools, which will result also in benefit of the Internet of the future. In Latin America, the organization responsible for Advanced Networks is CLARA (Latin American Advanced Networks Corporation). This corporation encourages institutions of higher education mainly to work in research and development of new information technologies and telecommunications. In Ecuador, CEDIA (Ecuadorian Consortium for Advanced Internet Development) directs and coordinates research projects that leverage the application of advanced technology focused on scientific and educational development of Ecuadorian society. The National University of Loja belongs to this Consortium, so must deal with the exploration of knowledge in accordance with this entity. The University has a data network topology extended star, distinguishing a public private area (radio, modle cisco and distance learning) and (Proxies areas, internal systems). The backbone uses fiber optics to connect to all areas except the A.E.I.R.N.N.R. (Department of Energy, Industry and Non-Renewable Natural Resources) which is linked via Dial-Up. Currently the local backbone of A.E.I.R.N.N.R. It has also migrated to optical fiber; like the rest of the network of the University, it is an extended star topology without redundant links.  We implemented the protocol in a network of evidence obtained significant differences between the current protocol IPv4 (Internet Protocol version 4) and IPv6 protocol. Using generation tools and traffic monitoring, we find that the protocols mentioned respond differently to situations of congestion (DNS servers, FTP, HTTP, Messaging and trafficking D-ITG), being IPv6 which optimizes the flow of network traffic .